2013
DOI: 10.1172/jci67087
|View full text |Cite
|
Sign up to set email alerts
|

Alveolar rhabdomyosarcoma–associated PAX3-FOXO1 promotes tumorigenesis via Hippo pathway suppression

Abstract: Alveolar rhabdomyosarcoma (aRMS) is an aggressive sarcoma of skeletal muscle characterized by expression of the paired box 3-forkhead box protein O1 (PAX3-FOXO1) fusion oncogene. Despite its discovery nearly two decades ago, the mechanisms by which PAX3-FOXO1 drives tumor development are not well characterized. Previously, we reported that PAX3-FOXO1 supports aRMS initiation by enabling bypass of cellular senescence checkpoints. We have now found that this bypass occurs in part through PAX3-FOXO1-mediated upre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
154
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 104 publications
(161 citation statements)
references
References 71 publications
7
154
0
Order By: Relevance
“…Both genetic and pharmacologic inhibition of YAP/TEAD and FOXM1 result in sarcoma cell proliferation defects, suggesting that these targets represent promising therapeutic interventions for mesenchymal tumors. Very recent studies have shown that YAP overexpression and function plays a role in the pediatric malignancies alveolar embryonal rhabdomyosarcoma (aRMS) and embryonal rhabdomyosarcoma (eRMS) (23,24). Together with these findings, we conclude that the Hippo pathway is potentially important in multiple sarcoma subtypes.…”
supporting
confidence: 75%
“…Both genetic and pharmacologic inhibition of YAP/TEAD and FOXM1 result in sarcoma cell proliferation defects, suggesting that these targets represent promising therapeutic interventions for mesenchymal tumors. Very recent studies have shown that YAP overexpression and function plays a role in the pediatric malignancies alveolar embryonal rhabdomyosarcoma (aRMS) and embryonal rhabdomyosarcoma (eRMS) (23,24). Together with these findings, we conclude that the Hippo pathway is potentially important in multiple sarcoma subtypes.…”
supporting
confidence: 75%
“…Imaginably, the cancer cells can secrete the intracellular netrin-1 and activate the receptors on the plasma membrane via autocrine, leading to YAP signaling regulation. It is also reported that YAP activity in modulation of proliferation and senescence is regulated by Ras association domain family 1A (RASSF1A) (28) and RASSF4 (29), respectively. The RASSF family of proteins consists of 10 members, most of which are considered as tumor suppressor proteins that undergo loss of expression through promoter methylation in various types of cancers.…”
Section: Discussionmentioning
confidence: 99%
“…Required for apoptosis and growth inhibition [8] Inhibits MST2 activity [93] Modulates the MAP kinase signal downstream of the Ras signal [77] K-Ras [8] ST1, MST2 [177] MST1 [75] Not available 5A (Nore1A) 1q32 47.1 kDa Suppresses tumour growth via apoptosis induction or cell cycle delay [7,82] Regulates microtubule formation [182] Induces degradation of HIPK1 oncoprotein [183] Required for the TNFa mediated apoptosis and full activation of MST1 [80] Ras, Carma1 [182,184] MST1 [43,177] MST2 [177] tubulin, Aurora A [182] Mdm2 [183] Itch [185] Yes [80] resistant to TNFa-induced apoptosis, fail to activate Mst1 in vivo 5C (Nore1B, RAPL) 1q32 30.4 kDa…”
Section: Kdamentioning
confidence: 99%
“…Current studies demonstrate that RASSF4 is broadly expressed in normal tissues [8,73,74] and the reduction of RASSF4 expression due to promoter specific hypermethylation was detected in tumor cell lines and primary tumors [8,73,74] suggesting that RASSF4 might act as a tumor suppressor. However, a recent paper revealed a pro-growth role for RASSF4 in alveolar rhabdomyosarcoma (aRMS) [75]. One of the subtypes of aRMS is characterized by paired box-3-forkhead box protein O1 (PAX3-FOXO1) -a chimeric protein, arising as a result of chromosomal translocation.…”
Section: Rassf4mentioning
confidence: 99%
See 1 more Smart Citation